Evaluation of skin sensitization induced by four ionic liquids. Issue 3 (28th August 2021) - Frawley, Rachel P.; Germolec, Dori R.; Johnson, Victor J.; Gulledge, Travis; Manheng, Wimolnut; White, Kimber; Shockley, Keith R.; Harris, Shawn F.; Hooth, Michelle; Ryan, Kristen
Abstract: Ionic liquids (ILs) are synthetic solvents used as replacements for volatile organic solvents. Human exposure occurs through dermal or oral routes. In rodents, several ILs were reported to induce dermal toxicity, irritation, and sensitization. Due to the potential for occupational exposure, and industrial use as nonvolatile solvents, 1‐ethyl‐3‐methylimidazolium chloride (EMIM, 6.25% to 50% v/v), 1‐butyl‐3‐methylimidazolium chloride (BMIM, 3.12% to 12.5% v/v), 1‐butyl‐1‐methylpyrrolidinium chloride (BMPY, 0.825% to 6.25% v/v), and N ‐butylpyridinium chloride (NBuPY, 0.825% to 12.5% v/v) were nominated to the National Toxicology Program and evaluated for skin sensitization. The test compound was applied to the ears of female BALB/c mice daily for 3 days in a primary irritancy (IRR)/local lymph node assay (LLNA). Sensitization was assessed in vitro in the direct peptide reactivity assay (DPRA), KeratinoSens™ assay, and human cell line activation test (h‐CLAT). In the LLNA, the butylated ILs, BMIM, and BMPY were more potent than NBuPY (butylated) or EMIM (ethylated), which was neither an irritant nor a sensitizer. NBuPY induced skin irritation in vivo at ≥3.12% ( p  ≤ 0.01), and sensitization in vitro in the KeratinoSens™ assay and h‐CLAT, but was negative for sensitization in vivo and in the DPRA. Although SI3 was not achieved, dermal treatment with 12.5% BMIM or 6.25% BMPY increased ( p  ≤ 0.01) lymph node cell proliferation in the LLNA. In vitro, BMIM was positive for sensitization in the h‐CLAT, and BMPY was positive in the h‐CLAT and KeratinoSens™ assay; both were negative in the DPRA. Integrated data analyses, weighted toward in vivo data, suggested that BMIM and BMPY may induce weak to mild sensitization. Abstract : Due to human dermal occupational exposure, and rodent dermal toxicity, 1‐ethyl‐3‐methylimidazolium chloride, 1‐butyl‐3‐methylimidazolium chloride (BMIM), 1‐butyl‐1‐methylpyrrolidinium chloride (BMPY), and N ‐butylpyridinium chloride (NBuPY) were evaluated for skin sensitization. In vitro, BMIM was positive in the human cell line activation test (h‐CLAT); BMPY and NBuPY were positive in the h‐CLAT and KeratinoSens™ assay. NBuPY induced skin irritation; BMIM and BMPY increased lymph node cell proliferation in the local lymph node assay, collectively indicating that BMIM and BMPY may induce weak to mild sensitization.